After print : eighteenth-century manuscript cultures - King, Rachael Scarborough (University of Virginia Press, 2020)
"While scholars have generally focused on the eighteenth century as a 'print culture, ' this book examines a range of manuscript practices--from letter writing to note taking to recipe preparation to novel authorship--to show how handwritten texts remained central to the media environment"--